2020
DOI: 10.35848/1347-4065/ab80a6
|View full text |Cite
|
Sign up to set email alerts
|

Solvation structure on water-in-salt/mica interfaces and its molality dependence investigated by atomic force microscopy

Abstract: Water-in-salt electrolytes (WiSEs), which contain salt with extremely high concentration (>20 mol kg−1), are attracting much interest as new electrolytes for energy storage systems, especially for lithium-ion batteries (LIBs), because they are considered to be suitable for developing safer systems. Structural analysis on WiSE/solid interfaces would provide beneficial information for developing LIBs. Whereas the interfacial structures of diluted aqueous electrolytes (less than 1 mol kg−1) have been intensively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 38 publications
(49 reference statements)
2
18
1
Order By: Relevance
“…Recently, atomic force microscope (AFM) measurements were reported by Ichii et al involving a similar WiS electrolyte containing a mixture of LiTFSI and lithium bis­(penta-fluoro­ethyl­sulfonyl)­imide (LiBETI). In those experiments, layering was observed with smaller structural dimensions than in our present measurements . Potential causes for these differences may lie in the different WiS electrolyte composition studied and the impact of the AFM tip geometry and chemistry.…”
contrasting
confidence: 64%
See 1 more Smart Citation
“…Recently, atomic force microscope (AFM) measurements were reported by Ichii et al involving a similar WiS electrolyte containing a mixture of LiTFSI and lithium bis­(penta-fluoro­ethyl­sulfonyl)­imide (LiBETI). In those experiments, layering was observed with smaller structural dimensions than in our present measurements . Potential causes for these differences may lie in the different WiS electrolyte composition studied and the impact of the AFM tip geometry and chemistry.…”
contrasting
confidence: 64%
“…In those experiments, layering was observed with smaller structural dimensions than in our present measurements. 36 Potential causes for these differences may lie in the different WiS electrolyte composition studied, and the impact of the AFM tip geometry and chemistry. It is also important to note that the AFM experiments output a 'resonant frequency shift' of the AFM cantilever, compared to the direct surface normal force (and therefore interaction free energy) measured in SFB.…”
mentioning
confidence: 99%
“…The present results were discussed in the context set by 3D AFM, however, the conclusions also apply for other AFM measurements performed in liquid [40,42,43,[61][62][63]. In general, neutral tips are recommended for generating force maps with a close relationship with the particle density distribution.…”
mentioning
confidence: 64%
“…That is, atomic-resolution AFM imaging was achieved in molten Ga. Although many studies on atomic-resolution AFM analysis in liquid environments have been reported, no AFM studies in molten metal have been performed. This is the first result showing that AFM has an atomic resolution in molten metal.…”
Section: Resultsmentioning
confidence: 99%
“…Quartz tuning fork (QTF) sensors have also been used as the AFM force sensors for investigations in liquids. They have also imaged surface topography on the atomic/molecular resolution , and have characterized interfacial solvation structures of aqueous solutions, ionic liquids, , and a polymeric liquid . Since the deflection of the QTF sensors is electrically detected using the piezoelectricity of the quartz, QTF sensors do not require optical transparency for the liquids.…”
Section: Introductionmentioning
confidence: 99%